Étude d'un tronçon de dédoublement de la RN 23 entre PK 379 et PK 385 - Megherbi, Djelloul; Mellal, Rachid, Directeur de thèse (My University, 2018)
This project presents study of unfolding of trunk RN 23 between tiaret and Laghouat by 6 km, study is composed of three parts: The first: the general description of the project with justification usols for fitting out Following the long Itinerary. The second: the choices of trace with alternatives one was devoted calculate of axis the Alignment includes, profile longitudinally and the profile transversely. The last: make drawing of the alignment includes understands profile longitudinally a profile transversally flows the calculation of cubature, the dimensioning road
Laghouat : Université Amar Telidji - Département de génie civil Option : Voies et ouvrages d'art